2020
DOI: 10.3982/qe1083
|View full text |Cite
|
Sign up to set email alerts
|

A narrative approach to a fiscal DSGE model

Abstract: Structural DSGE models are used for analyzing both policy and the sources of business cycles. Conclusions based on full structural models are, however, potentially affected by misspecification. A competing method is to use partially identified SVARs based on narrative shocks. This paper asks whether both approaches agree. Specifically, I use narrative data in a DSGE-SVAR that partially identify policy shocks in the VAR and assess the fit of the DSGE model relative to this narrative benchmark. In developing thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…To the best of our knowledge, bootstrap algorithms developed to construct confidence intervals in proxy SVARs only apply to strong instruments. Moreover,Lunsford and Jentsch (2016) show that the choice of bootstrap algorithms can yield very different confidence intervals for impulse responses.8 This feature is one major differentiation of our analysis from other Bayesian approaches-for example,Bahaj (2014) andDrautzburg (2016).…”
mentioning
confidence: 87%
“…To the best of our knowledge, bootstrap algorithms developed to construct confidence intervals in proxy SVARs only apply to strong instruments. Moreover,Lunsford and Jentsch (2016) show that the choice of bootstrap algorithms can yield very different confidence intervals for impulse responses.8 This feature is one major differentiation of our analysis from other Bayesian approaches-for example,Bahaj (2014) andDrautzburg (2016).…”
mentioning
confidence: 87%
“…Mertens and Ravn (2013) consider two particular decompositions: lower and upper triangular factorizations of S 1 S ′ 1 . While Drautzburg (2020) showed that certain policy rules justified these factorizations in the case of fiscal or monetary policy shocks, we are not concerned with policy shocks. We thus pursue a different type of identification.…”
Section: Identificationmentioning
confidence: 91%
“…See Drautzburg ((2020), appendix A.4) for closed‐form expressions of η , κ , and boldS1boldS1 in terms of the reduced‐form VAR covariance matrix boldVtrueboldB˜trueboldB˜.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…Secondly, this study relates to the Bayesian Proxy VAR literature, most directly to the small-scale Bayesian Proxy VAR model by Caldara and Herbst (2019) whose framework I extend to allow for latent factors. Other studies employing external instruments in the Bayesian paradigm are Drautzburg (2016) who estimates a narrative DSGE-VAR model, Bahaj (forthcoming) who applies high-frequency identification in a multi-country framework, and Arias et al (2018) who propose a Proxy VAR framework amenable to an importance sampler. Lastly, Kerssenfischer (2019) investigates the relation between informational insufficiency and identification in a frequentist setting.…”
Section: Introductionmentioning
confidence: 99%